THE TRAPEZOIDAL FINITE ELEMENT IN ABSOLUTE COORDINATES FOR DYNAMIC MODELING OF AUTOMOTIVE TIRE AND AIR SPRING BELLOWS. PART II: VERIFICATION - Dmitry POGORELOV (Transport Problems, 2021)
The second part of the paper includes numerical tests verifying equations of motion of flexible bodies in absolute coordinates with rectangle and isosceles trapezoid finite elements. The equations are formulated in the first part of the paper. The verification is based on three types of problems: calculation of natural frequencies and modes, evaluation of buckling, and computation of large static and dynamic deflections of flexible bodies. Tests show good agreement with the theoretical results and the results obtained by other authors.